Inflammation in the 21st Century - Kumar, Vijay; Aguilera Salgado, Alexandro; Shamsadin Athari, Seyyed (IntechOpen, 2022)
The present book includes 17 chapters covering different fields of inflammation that can be classified into acute or chronic in response to trauma, infection, and exposure to other noninfectious agents, including allergens and xenobiotics. Inflammation is a self-healing process, upon the clearance of the foreign particle and helps to protect the host. However, when it is not resolved and becomes chronic, it may lead to cancer and autoimmune diseases. This book includes different topics of autoimmune diseases, cancer, and other sterile inflammatory conditions originating in the absence of allergens as well as autoimmune disease and generates inflammatory immune response. Hence, the book will prove beneficial to researchers and scientists involved in inflammation research.